Compatibility of the urodynamic findings and mixed urinary incontinence symptoms - Fatemeh Mallah; Parvin Bastani; Aila Kari; Ehsan Sepehran; Hanieh Salehi-Pourmehr (Journal of Research in Clinical Medicine)
Introduction: Mixed urinary incontinence (MUI) is one of the most common problems of middle-aged women besides pelvic organ prolapses (POPs), and associated urinary symptoms are common disorders among older women whose treatment is necessary for the improvement of quality of life. This study aimed to evaluate the agreement between the symptoms of patients with MUI and urodynamic findings. Methods: This analytic cross-sectional study was conducted on 170 MUI patients who underwent urodynamic evaluation for confirmation of the presumptive diagnosis. Findings comprise patients with "voiding phase symptoms", "detrusor overactivity" (DO), "bladder hypersensitivity", and "stress urinary incontinence" (SUI). The Kappa coefficient was used to evaluate the agreement between the symptoms and urodynamic findings. Sensitivity, specificity, and agreement of symptoms with corresponding urodynamic findings were determined. Univariate logistic regression was used to estimate the predictive value of clinical history compared to urodynamic findings. Results: According to the results, the mean (SD) age of women was 51.87 (11.20). The mean bladder capacity was 339.6 (134.24), and post-void residual was 35.46 (43.89) ml. We determined a sensitivity of 75%, a specificity of 78.3%, a positive predictive value (PPV) of 86.3%, and a 63.2% negative predictive value (NPV) for SUI symptoms. According to the chi-square test results and Cohen Kappa values, there was no agreement between the symptoms of patients with MUI and bladder hypersensitivity, DO, and SUI. The only agreement was observed between the urinary frequency and voiding phase symptoms (Cohen kappa: 0.124; P value=0.003). Conclusion: There was no agreement between urodynamic findings and MUI symptoms except for urinary frequency and voiding phase symptoms. Since no comprehensive study has been conducted on the correlation between the symptoms of patients with MUI and urodynamic findings in our setting, the necessity to conduct large clinical studies is recommended.